Tindak Tutur Direktif dalam Pidato Politik Megawati Sukarnoputri pada Perayaan Hari Jadi PDIP ke 50 - Indah Utami Chaerunnisah (Balai Bahasa Provinsi Riau, 2023)
The objective of the research was to interpret the type and subtype of directive speech act found in Megawati Sukarnoputri’s political speech during the celebration of PDIP’s 50th anniversary, identify its frequencies and explain what they are used for. This is a qualitative research that applied directive speech act approach. The data in this study were taken from the transcript of the speech. They were interpreted by identifying utterances which applies directive speech act, and categorizing them into different types and subtypes. This research discovered 184 utterances which applied directive speech act where 121 of them were categorized as command, 35 were requests and 28 were suggestions. The most dominant subtype was direct speech act, while indirect speech used occasionally. It additionally revealed that command used to give order, instructions, prohibitions and warnings, requests to ask for cooperation, and support, and express wishes, and suggestions to give advice and opinions.